The Connicle curse : a Colin Pendragon mystery - Harris, Gregory (Fiction writer) (New York : Kensington Books, 2015)
"Victorian London's private detective Colin Pendragon learns that the cost of wealth can indeed be dear as he investigates the grisly fate of a well-heeled financier. When wealthy Edmond Connicle suddenly disappears, his distraught wife enlists the services of master sleuth Colin Pendragon and his loyal partner, Ethan Pruitt. Already on the case, however, is Scotland Yard's Inspector Varcoe. He suspects the Connicles' West African scullery maid of doing in her employer, especially when a badly burned body is discovered on the estate grounds with a sack of Voodoo fetishes buried beneath it. But all is not as it seems, and as more bodies are found, the pressure mounts on Varcoe, forcing him to forge an uneasy alliance with his nemesis, Pendragon. At the same time, Mrs. Connicle's fragile mental state appears increasingly more precarious. Could madness, not black magic, be at the root of these murders? To untangle the twisted truth, Pendragon and Pruitt must penetrate the hidden lives of the elite and expose the malevolent machinations of a ruthless kill...."--Publisher's website.
Keywords: Private investigators -- Fiction; Gay men -- Fiction; Murder -- Investigation -- Fiction; London (England) -- Social life and customs -- 19th century -- Fiction; Mystery fiction; Historical fiction